Islamic Organizational Citizenship Behavior among Millennial Workers: The Role of Islamic Leadership, Workplace Spirituality, and Islamic Work Ethic In Central Java, Indonesia - Rokhman, Wahibur (Ekonomi Syariah IAIN Kudus, 2022)
The objective of this study examined the influence of islamic leadership and workplace spirituality on organizational citizenship behavior among the millennial generation muslim employees in Central Java, Indonesia. Furthermore, the research also examined the role of islamic work ethic on organizational citizenship behavior. The questionnaires were distributed to Muslim millennial employees in Central Java in order to conduct a survey. For this study, a sample of 500 respondents was purposefully chosen, and 435 of those responses were returned and used. The variables and items were assessed using a five-point Likert scale. The data were further analyzed with multiple regression analysis. The results indicate that there is a significant positive effect of spiritual leadership and Islamic work ethic on organizational citizenship behavior. However, the study also found workplace spirituality does not influence organizational citizenship behavior. This study provides an understanding of the work behavior of the muslim millennial generation. This study will provide good insight for the organization to understand the role of Islamic leadership, workplace spirituality, and Islamic work ethic on organizational citizenship behavior among the millennial generation muslim employees in Central Java, Indonesia.